PUERTO RICO: THE COLLAPSE OF A COUNTRY. AN INITIAL REFLECTION ON THE DEMISE OF THE SUGAR INDUSTRY, PETROCHEMICALS, AND SECTION 936. - Alemán Iglesias, Javier (2020)
In this work, the main objective is to examine the socio-economic implications of the disintegration of the economy of Puerto Rico from the second half of the twentieth century, using as a center of study the cases of the sugar industry, the petrochemical industry (CORCO), and the industries under the section of 936 sector. The three sectors were at their peak and the most important activities in the Puerto Rican economy during the twentieth century; However, the three sectors were displaced and ruined by local and international situations, causing one of the largest economic crises in our contemporary history.